Efeito da adição da biomassa de Phormidium autumnale em filmes biodegradáveis de alginato de cálcio - Machado, Gloria Costa (Universidade Federal de São Carlos, 2022)
The present work proposed the development of biodegradable alginate films added with Phormidium autmnale biomass aiming for its food packaging and agriculture applications. Alginate films without and with the addition of microalgal biomass at different concentrations (0.06 and 0.1% w/v related to the polymeric solution), submitted or not to the homogenization, were produced and evaluated for their visual and morphological properties visual, thickness, transparency, moisture content, solubility, swelling degree (SD), water vapor permeability (WVP), chemical structure (FTIR), total nitrogen (TN) and total phenolics contents. The films exhibited a continuous and homogeneous polymeric matrix, with a characteristic greenish color in the films added with biomass. Biomass homogenization proved efficient in enhancing biomass distribution in the polymer matrix. The presence of microalgal biomass tended to increase the water solubility, WVP, SD, and TN content of films. It also reduced the transmittance and transparency of the films in the UV-Vis region. The films with biomass showed accentuated bands at 3235 cm-1 wavenumber, indicating the presence of phenolic compounds and lipids. The total phenolics content increased significantly in the films with microalgae compared to pure alginate film, indicating a possible antioxidant character of the films. The results demonstrate the excellent potential of the films in food packaging and agriculture applications.
Effect of Phormidium autmnale biomass addition in biodegradable calcium alginate films
Keywords: Microalga; Cianobactéria; Biopolímeros; Filmes biodegradáveis; Microalgae; Cyanobacteria; Biopolymers; Biodegradable films; ENGENHARIAS::ENGENHARIA DE MATERIAIS E METALURGICA::MATERIAIS NAO METALICOS::POLIMEROS, APLICACOES; ENGENHARIAS::ENGENHARIA QUIMICA::TECNOLOGIA QUIMICA::POLIMEROS